North Atlantic fishy feminists and the more-than-human approach: a conversation. Issue 12 (2nd December 2022) - Knott, Christine; Power, Nicole; Neis, Barbara; Frangoudes, Katia
Abstract: Fisheries and aquaculture have been the subject of feminist research and activism globally for decades. The result is a rapidly expanding body of literature examining women and fisheries and gender relations from oceans to plate. This body encompasses diverse and substantive critiques of mainstream fisheries research, policy and practice that ignore women's contributions showing how local practices, political economies and state policies (re)produce gender inequalities around access to fisheries resources and related wealth. Their work has had positive results. Some fishy feminist work draws on ecofeminism and feminist political ecology to explore links between resource degradation, neoliberal capitalism and patriarchy, but more needs to be done. This paper places existing North Atlantic feminist fisheries research in conversation with an emerging body of feminist scholarship interrogating human-fish relations. It makes the case for applying an ecofeminist lens in future work foregrounding how relations among humans, fisheries and fish are shaped by intersecting capitalist, colonial, speciesist and patriarchal systems of oppression. This lens would highlight the multiple oppressions that arise from altered fishery and aquaculture arrangements and dynamics in the age of the Anthropocene. Putting these bodies of work into lively conversation contributes to both the feminist fisheries/aquaculture and the more-than-human literatures.